Novel pathogenic variant (c.2947C > T) of the carbamoyl phosphate synthetase 1 gene in neonatal-onset deficiency - Ruimiao Bai; ALing He; Jinzhen Guo; Zhankui Li; Xiping Yu; JunAn Zeng; Yang Mi; Lin Wang; Jingjing Zhang; Dong Yang (Frontiers in Neuroscience, 2022)
BackgroundCarbamoyl phosphate synthetase 1 deficiency (CPS1D) is a rare autosomal recessive urea cycle disorder characterized by hyperammonaemia. The biochemical measurement of the intermediate metabolites is helpful for CPS1D diagnosis; it however cannot distinguish CPS1D from N-acetylglutamate synthetase deficiency. Therefore, next-generation sequencing (NGS) is often essential for the accurate diagnosis of CPS1D.MethodsNGS was performed to identify candidate gene variants of CPS1D in a Asian neonatal patient presented with poor feeding, reduced activity, tachypnea, lethargy, and convulsions. The potential pathogenicity of the identified variants was predicted by various types of bioinformatical analyses, including evolution conservation, domain and 3D structure simulations.ResultsCompound heterozygosity of CPS1D were identified. One was in exon 24 with a novel heterozygous missense variant c.2947C > T (p.P983S), and another was previously reported in exon 20 with c.2548C > T (p.R850C). Both variants were predicted to be deleterious. Conservation analysis and structural modeling showed that the two substituted amino acids were highly evolutionarily conserved, resulting in potential decreases of the binding pocket stability and the partial loss of enzyme activity.ConclusionIn this study, two pathogenic missense variants were identified with NGS, expanding the variants pectrum of the CPS1 gene. The variants and related structural knowledge of CPS enzyme demonstrate the applicability for the accurate diagnosis of CPS1D.